2021
DOI: 10.21273/hortsci15734-21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endogenous Hormones and Sugars on Fruit Size Driven by Cell Division between Korla Fragrant Pear and Its Bud Mutation

Abstract: Large-fruit bud mutations are important factors in fruit tree breeding. However, little is known about the differences between varieties and bud mutations. The ploidy identification of Korla fragrant pear (Pyrus sinkiangensis Yu) and its large bud mutation Zaomeixiang pear showed that the large-fruit characteristic was not caused by chromosome doubling. By counting mesocarp cells at different stages, we found that the number of cells increased continuously after pollination, and the difference was the greatest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Somatic mutations are mutations that occur in an organism's cell other than in a gamete, germ cell, or gametocyte (Jung et al, 2015). Most somatic mutations have no phenotypic effect, but some somatic mutations in plants can cause certain changes in leaf and branch shapes (Tian et al, 2021a). Somatic mutations have proved to be an important part of functional genetics research in model plants (Chatelet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Somatic mutations are mutations that occur in an organism's cell other than in a gamete, germ cell, or gametocyte (Jung et al, 2015). Most somatic mutations have no phenotypic effect, but some somatic mutations in plants can cause certain changes in leaf and branch shapes (Tian et al, 2021a). Somatic mutations have proved to be an important part of functional genetics research in model plants (Chatelet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Giovannoni et al (2017) also observed a gradual improvement in the sugars content in pear juice with fruit maturity. During the final stages of cell division, sucrose content is not required to provide energy, and some of the remaining monosaccharides are composited temporarily to sucrose, so the sucrose content increases slightly (Tian et al, 2021). An enhancement in total soluble sugars and reducing sugars at different fruit harvesting stages is attributed to the hydrolysis of polysaccharides to monosaccharides and also to the higher juice concentration, which causes loss of moisture through transpiration (Mesa et al, 2016).…”
Section: Carbohydrate Compositionmentioning
confidence: 99%